Un/desired impact of capital buffers: Evidence from Indonesian bank profitability and risk-taking - Muhammad Herru Hendrawan; Felisitas Defung; Wirasmi Wardhani (Cogent Economics & Finance, 2023)
The study employs a two-step system GMM technique within a panel data framework to investigate the effects of capital buffers on the profitability and risk behavior of Indonesian commercial banks from 2010 to 2020. The findings reveal that capital buffers serve a dual role, acting as a safety net against potential losses while also promoting increased financial stability and stronger shareholder engagement. This ultimately benefits the bank and its stakeholders in the long run. However, the positive effects of capital buffers come at a cost, as they are associated with reduced returns on assets and return on equity. The study emphasizes the importance of managing risk effectively, striking a delicate balance between risk-taking and prudent risk management to achieve optimal profitability. It underscores the need for banks to prioritize robust risk management practices and proper capitalization to avoid pursuing profitability at the expense of these critical factors. The study further highlights the significance of policymakers finding the right equilibrium between promoting financial stability through capital requirements and fostering a competitive banking industry that can generate profits and support economic growth.
Keywords: G21; G28; G32; 330; banking regulation and supervision; capital buffers; profitability; risk